2020
DOI: 10.3390/cancers12010141
|View full text |Cite
|
Sign up to set email alerts
|

Mutant IDH1 Depletion Downregulates Integrins and Impairs Chondrosarcoma Growth

Abstract: Chondrosarcomas are a heterogeneous group of malignant bone tumors that produce hyaline cartilaginous matrix. Mutations in isocitrate dehydrogenase enzymes (IDH1/2) were recently described in several cancers, including conventional and dedifferentiated chondrosarcomas. These mutations lead to the inability of IDH to convert isocitrate into α-ketoglutarate (α-KG). Instead, α-KG is reduced into D-2-hydroxyglutarate (D-2HG), an oncometabolite. IDH mutations and D-2HG are thought to contribute to tumorigenesis due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Reprogramming of energy metabolism and evading immune destruction are two emerging hallmarks of cancer, providing new insights for cancer therapy [21]. With the recent discovery of specific mutations in metabolic enzymes in certain cancer types, metabolic pathway are increasingly considered as source of new targets [22]. Meanwhile, treatment of cancer has been revolutionized by immunotherapy with currently widely used checkpoint inhibitors against regulatory immune checkpoint molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprogramming of energy metabolism and evading immune destruction are two emerging hallmarks of cancer, providing new insights for cancer therapy [21]. With the recent discovery of specific mutations in metabolic enzymes in certain cancer types, metabolic pathway are increasingly considered as source of new targets [22]. Meanwhile, treatment of cancer has been revolutionized by immunotherapy with currently widely used checkpoint inhibitors against regulatory immune checkpoint molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation induced cell death releases intracellular adenosine into the extracellular environment, and also releases ATP, which can be hydrolyzed into adenosine via CD39/CD73 pathway [26]. On the other hand, radiation can activate DNA repair, which is an energy-consuming process and finally promote ATP consumption and increase adenosine production [22,27]. Therefore, the enriched adenosine level might result from three aspects: i) direct release of intracellular adenosine, ii) activation of DNA repair and iii) hydrolysis of tumor cell-released ATP via the CD39/CD73 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In ChS, several repetitive point mutations have been described. The most common are mutations in IDH1 and IDH2 genes, which encode isocitrate dehydrogenase 1 and 2, an enzyme that converts isocitrate to α-ketoglutarate (αKG) [ 77 , 78 ]. Somatic mutations of IDH1 and IDH2 result in higher production of 2-hydroxyglutarate (2HG), one of the oncometabolites [ 79 , 80 ] from αKG.…”
Section: Mutations In Chondrosarcomamentioning
confidence: 99%
“…Isocitrate dehydrogenase (IDH) is an important metabolic enzyme in the tricarboxylic acid cycle, whose mutated genes are associated with a variety of tumors, including acute myeloid leukemia (AML), glioma, cholangiocarcinoma, colon cancer and chondrosarcoma (5). IDH mutation can catalyze the conversion of a-ketoglutarate (a-KG) to 2-hydroxyglutarate (2-HG) (Figure 1), and studies have found that the level of 2-HG in cancer patients is higher than that in normal or non-mutated cancer patients (6)(7)(8). The increased level of 2-HG and the resulting epigenetic disorders and cell differentiation show the potential carcinogenicity of IDH mutations (9).…”
Section: Introductionmentioning
confidence: 99%